2015
DOI: 10.1007/s10498-015-9261-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Rates of Biogenic Carbonates in Natural Seawater at Different pCO2 Conditions: A Laboratory Study

Abstract: The bulk dissolution rates of six biogenic carbonates (goose barnacle, benthic foraminifera, bryozoan, sea urchin, and two types of coralline algae) and a sample of mixed sediment from the Bermuda carbonate platform were measured in natural seawater at pCO 2 values ranging from approximately 3000 to 5500 latm. This range of pCO 2 values encompassed values regularly observed in porewaters at a depth of a few cm in carbonate sediments at shallow water depths (\15 m) on the Bermuda carbonate platform. The biogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
(112 reference statements)
2
13
0
Order By: Relevance
“…6 mole-% Mg) had higher dissolution rates than the more Mg-rich coralline red algae (> 20 mole-% Mg). Pickett and Andersson (2015) also observed that crushed specimens of bryozoa had faster dissolution rates than crushed specimens of coralline red algae, despite the bryozoa's lower Mg-content. They attributed this trend to the bryozoan skeletons possessing proportionally more microstructural surface area than the coralline algae.…”
Section: Effect Of Caco 3 Polymorph Mineralogy On Gross Dissolution Rmentioning
confidence: 85%
See 4 more Smart Citations
“…6 mole-% Mg) had higher dissolution rates than the more Mg-rich coralline red algae (> 20 mole-% Mg). Pickett and Andersson (2015) also observed that crushed specimens of bryozoa had faster dissolution rates than crushed specimens of coralline red algae, despite the bryozoa's lower Mg-content. They attributed this trend to the bryozoan skeletons possessing proportionally more microstructural surface area than the coralline algae.…”
Section: Effect Of Caco 3 Polymorph Mineralogy On Gross Dissolution Rmentioning
confidence: 85%
“…A smaller body of work has investigated the dissolution kinetics of biogenic CaCO 3 minerals. The majority of these studies have focused on the dissolution kinetics of bulk CaCO 3 sediments, often with the aim of constraining reactions involved in the evolution of sedimentary porewater, early-to-late stage sedimentary diagenesis, lithification, and sedimentary buffering of the seawater carbonate system (Andersson et al, 2007;Andersson et al, 2009;Archer et al, 1989;Balzer and Wefer, 1981;Berger, 1967;Dreybrodt, 1985a, 1985b;Burdige et al, 2008Burdige et al, , 2010Burdige and Zimmerman, 2002;Boucher et al, 1998;Friedman, 1964;Gehlen et al, 2005aGehlen et al, , 2005bHales and Emerson, 1996;Hales et al, 1994;Honjo and Erez, 1978;Jahnke and Jahnke, 2004;Kinsey, 1985;Langdon et al, 2000;Leclercq et al, 2002;Milliman, 1978;Morse, 1978;Morse et al, 2006;Peterson, 1966;Pickett and Andersson, 2015;Rude and Aller, 1991;Silverman et al, 2007aSilverman et al, , 2007bSchmalz, 1965;Tynan and Opdyke, 2011;Walter et al, 1993;Walter and Burton, 1990;Yates and Halley, 2006). These studies generally investigate bulk mixtures of biogenic CaCO 3 minerals that, in some cases, have been substantially altered 196 themselves through neomorphism, diagenetic conversion, laboratory cleaning, and/or natural loss of organic impurities and protective organic layers.…”
Section: Overview Of Prior Work On the Dissolution Kinetics Of Cacomentioning
confidence: 99%
See 3 more Smart Citations